Political Ecology in a Yucatec Maya Community - Anderson, E. N., 1941- (Book collections on Project MUSE., 2005)
"As Anderson observes, traditional Maya management, with its immense knowledge base, remains the best - indeed, the only - effective system for making a living from the Yucatan's harsh landscape. Political Ecology in a Yucatec Maya Community is a compelling testament to the daily life practices of modern peasant farmers that can provide us with clues about more efficient management techniques for the conservation of biodiversity worldwide."--Jacket.